The Form of Morphemes: MEG Evidence From Masked Priming of Two Hebrew Templates - Kastner, Itamar; Pylkkänen, Liina; Marantz, Alec (Frontiers in Psychology, 2018)
Studies of lexical access have benefited from comparisons between languages like English, which shows concatenative morphology, and Semitic languages showing non-concatenative morphology of roots and patterns. Morphological decomposition in Semitic has previously been probed using masked priming, originally developed to investigate concatenative morphology. However, studies on Semitic have often targeted Semitic-specific questions, such as whether the root and the verbal template prime lexical access. The overall consequence of these studies for our understanding of lexical access remains unclear. In two experiments on Hebrew using MEG, we demonstrate that a verbal form which is orthographically and phonologically indistinguishable from non-verbal forms is primed by other verbs in the same template but not by similar nouns and adjectives. These results suggest that masked priming taps into more than just visual forms but reflects morphological content, even if this content is abstract, showing no distinct orthographic or phonological marking.